P.005 Long-term retention on adjunctive brivaracetam in adults with focal seizures and previous carbamazepine, lamotrigine, levetiracetam, or topiramate use: Post-hoc analysis. (June 2019) - Foris, K; Martin, M; Dimova, S; Elmoufti, S; Laloyaux, C; Chung, SS
Abstract : Background: Previous post-hoc analysis of three 12-week, double-blind, placebo-controlled trials of adjunctive brivaracetam (BRV) in patients with focal seizures demonstrated similar efficacy over placebo regardless of previous carbamazepine (CBZ), lamotrigine (LTG), levetiracetam (LEV), or topiramate (TPM) failure. This analysis explored long-term retention of adjunctive BRV in patients with previous CBZ/LTG/LEV/TPM. Methods: Post-hoc analysis of double-blind, placebo-controlled trial (N01358 [NCT01261325]) and open-label extension (N01379 [NCT01339559]; cut-off 15-March-2017) of adjunctive BRV in patients (≥16 years) with focal seizures. Outcomes were assessed in patients randomized to BRV (100 or 200 mg/day) who had previous CBZ/LTG/LEV/TPM (stopped ≥90 days before BRV initiation). Results: 503 patients were analyzed. Baseline characteristics were generally similar in subgroups with previous CBZ/LTG/LEV/TPM (n=209/162/256/182). Overall, Kaplan-Meier-estimated BRV retention at 1-, 3-, and 5-years was 71.0%, 50.9%, and 32.4%. Across previous antiepileptic drug (AED) subgroups, Kaplan-Meier-estimated BRV retention (1-year: 64.8%–73.2%; 3-year: 41.9%–49.9%; 5-year: 31.5%–35.7%), BRV discontinuations (58.4%–63.0%), and most common reasons for discontinuation (lack of efficacy: 23.0%–25.3%; adverse event: 16.7%–22.2%) were generally similar. Conclusions: Post-hoc analysis demonstrated similar long-term retention rates and discontinuation reasons with adjunctive BRV in adults previously treated with CBZ/LTG/LEV/TPM. Adjunctive BRV provides long-term effectiveness in patients who failed common AED treatments, including LEV. UCB Pharma-sponsored